Parental gender stereotypes and student wellbeing in China - Shuai Chu; Xiangquan Zeng; Klaus F. Zimmermann (University of Bonn, Center for Development Research (ZEF), 2020)
Non-cognitive abilities are supposed to affect students' educational performance, who are challenged by parental expectations and norms. Using standard econometric techniques, parental gender stereotypes are shown to strongly decrease student wellbeing in China. Students are strongly more depressed, feeling blue, unhappy, not enjoying life and sad while parental education does not matter. The relationships though dealing with a gender-specific issue do not exhibit gender-specific differences: Neither does it matter who the parent is, nor whether the kid concerned is a boy or a girl. Parental stereotypes may undermine girls' selfconfidence and make them more prone to anxiety and other mental health issues. For boys, stronger stereotypes may indicate higher expectations and pressures, which also generate negative emotions.
Keywords: I12; I26; I31; J16; 330; Gender identity; gender stereotypes; student wellbeing; non-cognitive abilities; mental health; subjective wellbeing